LAW IS NOT A PROFESSION FOR COWARDS: REPRESENTATIONS AND DISCOURSES ABOUT PROFESSIONAL LIFE IN AN INSTAGRAM PROFILE - Nuñez, Izabel (2023)
This paper aims to understand how professional practice of criminal lawyers representations are triggered, according to the content analysis of an instagram profile focused on young lawyers. Also, it explains social values and representations about criminal law practice. In order to do so, an online ethnography was conducted. As results, were identified an appreciation for tradition, as something that ranks criminal lawyers, as well as the depreciation of an ostentatious posture. Through the empirical material analysis we highlight the categories that are connected to this social group professional activity.